Field reports, John Van Dyk, fall 1990 - Van Dyk, John, 1936-et al (1990)
Field reports with detail about sighting and weather notes submitted in a letter from John Van Dyk to Carl Bendorf on December 1, 1990. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1990. Epson - sheet feed